Analysis of types of innovation in micro and small-sized enterprises: a case study in Barranquilla, Colombia (2024)
Current market conditions require continual adaptation from companies. Therefore, it is necessary to develop strategies and innovations to be competitive, and Micro, Small and Medium-sized Enterprises (MSMEs) are not exempt from this reality. Therefore, this work aims to analyze the forms of innovation in the company and their contribution to the innovation capability in the context of MSMEs. Four types of innovation were evaluated: product innovation, process innovation, organizational innovation, and marketing innovation. A structural equation model was implemented through nine dimensions measured in 207 micro and small companies in Barranquilla, Colombia. The main findings showed statistical significance from the dimensions studied on the dynamic innovation capability.